Effect of oral contraceptives on tear film in reproductive age group women - Sharma, Amita; Porwal, Surabhi; Tyagi, Manoj (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: According to WHO 2009, 60-70% women use one of the method of contraception. 8.8% to 15.4% women use oral contraceptives. Objective of present study was to investigate the effect of oral contraceptives on androgen profile and tear film parameters in females within child bearing age. Methods: Present study involve 100 healthy women between 20-45 years, who presented in family planning clinic. Two groups were made according to the use of oral contraceptive pills. Study group consist of 50 women who were on OCPs (Oral contraception pills) and 50 as control group were not taking any hormonal contraceptives. Serum testosterone and DHEA levels of all subjects was done by Enzyme Immuno Assay on blood samples which were collected during 3th to 7th day of menstrual cycle. Quantitative test for tear secretion was done by Schirmer’s test. Stability of tear film was measured by Tear Breakup time (TBUT). Statistical analysis was done to determine the correlation between use of OCPs and androgen profile and tear film parameters. Results: Present results shows decreased androgen levels in women taking oral contraceptives as compared with age matched women who were not taking oral contraceptives. Tear secretion was significantly reduced in study group as indicated by decreased Schirmer’s test values in study group as compared to control group, the tear film stability was also significantly decreased in women taking oral contraceptives. Conclusions: Present study suggest that androgen profile decrease in women taking oral contraceptives. These results support that use of oral contraceptives may be an important etiological factor in pathogenesis of dry eye disease reproductive age group women.